Slow breathing for reducing stress: The effect of extending exhale. (May 2023) - Birdee, Gurjeet; Nelson, Katrina; Wallston, Ken; Nian, Hui; Diedrich, Andre; Paranjape, Sachin; Abraham, Robert; Gamboa, Alfredo
Abstract: Introduction: Slow breathing techniques are commonly used to reduce stress. While it is believed by mind-body practitioners that extending the exhale time relative to inhale increases relaxation, this has not been demonstrated. Methods: We conducted a 12-week randomized, single-blinded trial among 100 participants to compare if yoga-based slow breathing with an exhale greater inhale versus an exhale equals inhale produces measurable differences in physiological and psychological stress among healthy adults. Results: Participants mean individual instruction attendance was 10.7 ± 1.5 sessions out of 12 offered sessions. The mean weekly home practice was 4.8 ± 1.2 practices per week. There was no statistical difference between treatment groups for frequency of class attendance, home practice, or achieved slow breathing respiratory rate. Participants demonstrated fidelity to assigned breath ratios with home practice as measured by remote biometric assessments through smart garments (HEXOSKIN). Regular slow breathing practice for 12 weeks significantly reduced psychological stress as measured by PROMIS Anxiety (−4.85 S.D. ± 5.53, confidence interval [−5.60, −3.00], but not physiological stress as measured by heart rate variability. Group comparisons showed small effect size differences (d = 0.2) with further reductions in psychological stress and physiological stress from baseline to 12 weeks for exhale greater than inhale versus exhale equals inhale, however these differences were not statistically significant. Conclusion: While slow breathing significantly reduces psychological stress, breath ratios do not have a significant differential effect on stress reduction among healthy adults. Highlights: Slow breathing techniques are commonly used to reduce stress. Slow breathing reduces psychological but not physiological stress as measured by heart rate variability among healthy adults. Extending exhale versus inhale while slow breathing does not significantly affect stress reduction among healthy adults.